Estrogen: the forgotten player in metaflammation - Zhu, Bao-Ting; Liao, Qing-Qing; Tian, Hai-Ying; Yu, Dao-Jiang; Xie, Teng; Sun, Xi-Lu; Zhou, Xin-Meng; Han, Ying-Xuan; Zhao, Yu-Jie; El-Kassas, Mohamed; Liu, Xiu-Xiu; Sun, Xiao-Dong; et al. (Frontiers in Pharmacology, 2024)
Metaflammation is low-grade inflammation triggered by chronic metabolic imbalance and caused by dysregulated metabolites in metabolic inflammatory syndrome (MIS), which includes four diseases: obesity, type 2 diabetes mellitus (T2DM), atherosclerosis (AS), and nonalcoholic fatty liver diseases (NAFLD, recently proposed to be replaced by metabolic dysfunction-associated steatotic liver disease, MASLD). These diseases exhibit apparent sex dimorphism as regards MIS. Estrogen not only plays a crucial role in gender differences in adults but also possesses an antiinflammatory effect on many metabolic diseases. In this study, we present a prediction of the differential proteins and signal transduction of estrogen in MIS through network pharmacology and review the validated studies on obesity, T2DM, AS, and NAFLD. Subsequently, we compared them to obtain valuable targets, identify current gaps, and provide perspectives for future research on the mechanisms of estrogen in metaflammation.